Formulation, characterization, and optimation of emulsion fuel - Fatin Nadhirah, Mahazan (2013)
This research presents formulation, characterization, and optimization study of emulsion fuel. Different types of surfactants, ratios of surfactants, and water/oil ratios were used. Types of surfactants used were Span-80, Triton X-100, and SDDS. The ratios used for each surfactant was 1.0%, 1.5%, and 2.0%. The ratios of water/oil used were 20/80, 30/70, and 40/60. The samples were prepared by dissolving surfactant in the oil, followed by addition of water. The samples were agitated using three-bladed propeller to disperse the water in the emulsion. Two types of tests were done to the samples; the first is stability test, and the second is viscometer test. Stability test was done with the duration of five to six days, and data of shear rate, shear stress, torque, and viscosity were recorded via viscosity test. Viscosity test was done for 30°C, 50°C, and 70°C with rpm of 20, 30, 50, and 30. Results from observation and viscometer test suggest that Span-80 with 2% surfactant and 20/80 water ratio is the most stable emulsion. Results from this work may be useful for further development of emulsion fuel.